2021
DOI: 10.1109/access.2021.3076119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Assessments of Machine-Learning Methods for Artificial Seismic Sources Discrimination

Abstract: Mankind is vulnerable to artificial seismic sources and accompanying explosions' consequences. Recently, seismicity catalog contamination is among the main problems faced by seismologists. Since identifying artificial seismic sources is the first and always challenging stage, it is imperative to develop an automated control system that will discriminate tectonic from non-tectonic events. Detection and removal of the artificial seismic sources have become urgent. Early treatments and cleaning of contaminated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…A large number of scholars [1][2][3][4] have conducted related studies on the analysis of the blasting vibration effect of mountain tunnels. Qin and Zhang [5] found that there is a good fitting relationship between the peak blasting vibration velocity and the total charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of scholars [1][2][3][4] have conducted related studies on the analysis of the blasting vibration effect of mountain tunnels. Qin and Zhang [5] found that there is a good fitting relationship between the peak blasting vibration velocity and the total charge.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8] elaborated the blasting vibration control of a three-dimensional intersection tunnel in detail and achieved a good control effect. In addition, modern technologies [2] represented by machine learning [9] are also widely used in research in this field. Hasanipanah et al [10] made a prediction and analysis of ground vibration caused by blasting construction based on particle swarm optimization and achieved good results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the four evaluation metrics, we also visualize the detection effect through ROC curves and confusion matrices. The ROC curve indicates the trade-off between the TP rate and the FP rate of the estimated classes [48], and the confusion matrix is composed of TP, TN, FP, and FN. The model size and number of parameters are chosen for evaluation in terms of the lightweight property to determine how lightweight the model is.…”
Section: A Implementationmentioning
confidence: 99%
“…Due to the limitations of traditional techniques, ML tools may be used to generate (learn) extremely complex relational models. Several difficult research issues, from recommendation systems to autonomous driving automobiles, have been successfully addressed by the use of ML approaches [15], [16], [17]. This success is credited to the adaptability of ML in understanding complicated systems and to the fact that all you need to execute your ML algorithm are a proper ML model and adequate datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Data mining and reassembling irregular or missing data using ML is another useful application of ML. In [17] and [16], ML algorithms have been proposed to assess the peak particle velocity (PPV) and discriminate the quarry blasts. The peak ground acceleration and its impact on urban planning have both been predicted using ML [36].…”
Section: Introductionmentioning
confidence: 99%